Conflicting logics within the real estate industry How real estate companies navigate green investments and tensions between profitability and sustainability - Skoghäll, Tilda; Windh, Anna (My University, 2024)
The built industry is responsible for 42% of the world's annual CO2 emissions, which makes it one of the most significant contributors to global warming. Adapting to sustainable practices is therefore one of the most pressing challenges facing the industry in this century. One strategy to handle this challenge is to make investments that have a positive impact on the environment, commonly referred to as green investments. The aim of this thesis is to investigate how companies in the residential real estate industry navigate the potential tensions between profitability and sustainability when considering new investments. The thesis is based on a case study, employing a qualitative research design. The data was collected through semi-structured interviews with the case company, an investment advisory company focused on residential real estate, and its portfolio companies. The study starts from the premise that real estate companies are influenced by two different logics: the logic of the market and the logic of the environment. Regarding market logic, it was established that the real estate industry is characterised by investor requirements and sustainability regulations that compel companies to make green investments. Additionally, customers are unwilling to pay a premium for a sustainable home which creates difficulties for companies trying to adjust to these conflicts between regulations and customers. To succeed in this challenging environment, companies must integrate sustainability across their operations and identify innovative ways to invest without increasing costs for tenants. Regarding environmental logic, it has been observed that a greater proportion of companies in the industry are making green investments. This is indicative of a growing norm within the industry, whereby an increasing number of companies are focusing on sustainability work and green investments. Furthermore, the focus is not solely on economic profitability, it also encompasses the willingness to do good. Finally, the interviews revealed that many of the institutional elements of the environmental logic have influenced the market logic, leading to the conclusion that sustainability is no longer an optional consideration for companies, but rather a necessity for maintaining competitiveness.
Keywords: Green investments; integration of sustainability; real estate industry; institutional theory; institutional logics; market logic; environmental logic